Rainfall analysis for rainwater harvesting in Politeknik Ungku Omar - Mazlina Alang Othman; Hasliza Zulkifli (Penerbit Universiti Kebangsaan Malaysia, 2022)
Rainwater Harvesting System (RWHS) is a collection and storage of rainwater for future use and have many benefits related to the economy, environment, technology, and society. Malaysia is well positioned to harvest rainwater because of number of rainy days in Malaysia is high and average of rainfall amount 2500 mm annually. Because of the effects of the topography of Peninsular Malaysia, rainfall distribution varies significantly. Thus, rainfall data analysis for rainwater harvesting potential should be made based on local climate and influences from the monsoon. The objective of this study was to analyse the rainfall data for rainwater harvesting potential in Politeknik Ungku Omar (PUO). To simplify analysis, rainfall distribution is discussed within two monsoons which is Southwest monsoon and Northeast monsoon while rainfall trend is determined under the year 2000 to 2019. The result indicates that PUO will be potential for RWHS regarding to high number of rainfalls event and increasing trend in annual rainfall amount in that area. Further research is clearly needed to investigate the roof size and water consumption to increase the effectiveness of the RWHS.